REMOTE WORKING IN GREECE DURING THE COVID-19 PANDEMIC: HOW IT AFFECTED EMPLOYEES AND BUSINESS - Andreas Karaoulanis (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The covid-19 pandemic has created the necessity for quick and robust solutions to help professionals and businesses survive the lockdowns. Remote working was one of these solutions and played a crucial role for both employees and businesses to help them overcome the challenges that the pandemic posed. This research attempted to shed some light on special issues that have to do with remote working and its impact on both employees and businesses by unveiling specific problems that the participants faced during this stressful period. The research followed the survey method using a random and convenient sample of respondents. The questionnaire was filled with open-ended questions and disseminated via email. Qualitative analysis was applied to process the collected data. The results showed that remote working had a mainly positive impact on people during the pandemic. However, both the employees and the business faced several challenges. Most businesses and people were unprepared to face such a situation. Thus, many problems occurred.